Family patterns, attitudes and behaviour in relation to the upbringing of children in South Korea: the social construction of child abuse - Yang, Sonam (2005)
This study explores the ways in which the Western concept of child abuse is understood by parents and professionals in Korea and how it is applied to Korean society. In order to address this, attention will be focused on parents' and relevant professionals' attitudes and perceptions in relation to child rearing, along with their responses to the problem of child abuse.